Interviewing children about sexual abuse controversies and best practice - Faller, Kathleen Coulborn (New York ; Oxford : Oxford University Press, 2007)
A core issue for professionals responsible for addressing sexual abuse is how to correctly identify cases. 'Interviewing Children About Sexual Abuse' critically reviews research and practice on the spectrum of issues related to interviewing the sexually abused child.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Child sexual abuse -- Investigation -- United States; Interviewing in child abuse -- United States; Sexually abused children -- United States